The Effect of Medical Therapy on IOP Control in Ghana - Gyasi, M E (Ghana Med J, 2014)
BACKGROUND: To investigate IOP control following twelve months of continuous medical therapy in Ghana. METHODS: This retrospective case series included 163 glaucoma patients diagnosed at a referral eye center between 1996 and 2006. Information collected included age, gender, IOP at presentation, six months and one year post treatment and types of anti-glaucoma medications prescribed. Optimal IOP control was defined according to results from the Advanced Glaucoma Intervention Study (AGIS), which demonstrated arrest of visual field progression in patients with IOP < 18 mmHg at all visitations: Level 1 (post-treatment IOP ≤ 21 mmHg); Level 2 (≤ 18 mmHg) and level 3 (≤ 16 mmHg). The principal outcome measure was the achievement of IOP <18 mmHg at six months and twelve month visitations. RESULTS: One hundred sixty three patients were analyzed. These included 68 males (41.7%) and 95 females (58.3%). The mean age was 57±16 (median 59 years; range 7 – 95 years). There was no significant difference in age (p=0.35) or mean IOP (p=0.08) between genders. The mean pre-treated IOP of 31.9±8.9 mmHg significantly decreased to 21.3±6.6 mmHg at 6 months (p=0.001), with 57.4% of eyes at Level 1 IOP control, 25.3% at Level 2 and 15.4% at Level 3 and decreased further at 12 months to 20.7±6.9 mmHg (p=0.48) with 69.7% of eyes at Level 1, 34.4% at Level 2, and 12.4% at Level 3. CONCLUSIONS: Current medical regimen is insufficient to reduce IOP to target levels as defined in the Advanced Glaucoma Intervention Study.